Penile prosthesis in the management of erectile dysfunction following cancer therapy - Dadhich, Pranav; Hockenberry, Mark; Kirby, E. Will; Lipshultz, Larry (Translational Andrology and Urology, 2017)
Erectile dysfunction (ED) is a common problem in older men and occurs with even greater frequency following the treatment of pelvic malignancies. Inflatable penile prosthesis (IPP) implantation is a safe and effective form of definitive ED treatment for those men who fail more conservative measures, and it can be used with similar outcomes in men following cancer therapy. Although many of these men remain dissatisfied with other therapeutic options for ED, IPPs are underutilized in this population. This review will discuss the current practice patterns, outcomes and nuances to surgical technique regarding the use of IPPs in patients with ED following cancer therapy.